PENGELOLAAN OBJEK WISATA PANTAI TANJUNG PENDAM BERDASARKAN DINAMIKA KUNJUNGAN WISATAWAN - ALDINO AKBAR (Akuatik: Jurnal Sumberdaya Perairan, 2008)
Tourist is one of main component of management in Tanjung Pendam Beach Resort which is oriented to mass tourism as funding source for the continuity of the resort. That’s why, it’s important to know the dynamic of the tourists so it can be determined better form of the management to increase the quality of the services that can impact to the increasing of quantity of the tourists. Methode is used in this research is direct observation with combination of the factually data record and interpretative data record in recording the obserbed data. The data summary of the visitor is recorded most are observed in the working day from Monday to Saturday, the data in a row are : 127, 140, 133, 110, 75, 97 persons. But, on Sunday there are only 65 tourists recorded. The number of ticket sold is most on Sunday, as many as 205 tickets sold. Vehicles that is dominantly used by the tourists to reach the location of the resort is motorcycle with the highest amount is 116 on Sunday. The tourists are prefer to visit in cloudy weather as many as 161 tourist than hot, dark cloudy and rainy weather with the visitors in a row are 102, 104 dan 19 person.